Hydroxyapatite nanocrystals as a smart, pH sensitive, delivery system for kiteplatin. Issue 33 (11th July 2016) - Lelli, Marco; Roveri, Norberto; Marzano, Cristina; Hoeschele, James D.; Curci, Alessandra; Margiotta, Nicola; Gandin, Valentina; Natile, Giovanni
Abstract : Synthetic hydroxyapatite nanocrystals are proposed as a pH-sensitive carrier capable to release an antitumor platinum-drug selectively at the tumor site. Abstract : Hydroxyapatite (HA) nanocrystals are important inorganic constituents of biological hard tissues in vertebrates and have been proposed as a bone substitute or a coating material for prostheses in biomedicine. Hydroxyapatite is also amenable for its capacity to bind to a great variety of biomolecules and therapeutic agents. As drug carriers, apatite nanoparticles also have the advantage of pH dependent solubility and low toxicity. Thus HA nanoparticles are negligibly soluble at physiological pH but their dissolution is accelerated at lower pH such as that typically found in the vicinity of tumors. In the present study we have investigated the adsorption on and the release from biomimetic HA nanoparticles of two platinum derivatives of cis -1, 4-diaminocyclohexane ([PtX2 ( cis -1, 4-DACH)], X2 = Cl2 (1 ) and 1, 1-cyclobutanedicarboxylate (CBDCA, 2 )). The first of the two compounds proved to be active against colon cancer cells also resistant to oxaliplatin. The release has been investigated as a function of pH to mimic the different physiological environments of healthy tissues and tumors, and the in vitro cytotoxicity of the releasates from the HA matrices has been assessed against various human cancer cell lines. The results fully confirmed the potential of1 -loaded HA nanoparticles as bone-specific drug delivery devices.